HOMOPHOBIA: A PRELIMINARY DIAGNOSIS OF A PENDING SUBJECT - Garcés Marrero, Roberto (Revista Sexología y Sociedad, 2016)
IN CUBA, THERE ARE VERY FEW SCIENTIFIC STUDIES BASED ON HOW HOMOPHOBIA IS EXPRESSED. THE CURRENT RESEARCH AIMS TO DO A HOMOPHOBIA DIAGNOSIS AMONG 210 SELECTED PEOPLE IN ORDER TO KNOW, FIRSTLY, WHAT THEY UNDERSTAND BY HOMOPHOBIA; SECONDLY, HOW MANY OF THEM HAVE BEEN VICTIMS OR WITNESSES OF IT; AND LASTLY, IN WHICH WAY THEY HAVE EXPERIENCED IT (I.E., WHERE, WHEN, HOW, BY WHOM, THE EFFECTS AT PERSONAL LEVEL, AND THEIR REACTIONS). TO THIS EFFECT, A QUESTIONNAIRE, FROM A QUANTITATIVE AND QUALITATIVE PERSPECTIVE, TO MEMBERS OF THE COMMUNITARIAN SOCIAL NETWORKS OF THE NATIONAL CENTER FOR SEXUAL EDUCATION AND SOME COLLABORATORS HAS BEEN CARRIED OUT. IT AIMS TO BE THE FIRST PART OF A WIDER RESEARCH PROCESS ALLOWING A PROPOSAL FOR A SYSTEM OF ACTIONS TO TRANSFORM THIS SOCIAL PHENOMENON, GIVEN THAT MORE THAN 80% QUESTIONED PEOPLE HAVE BEEN WITNESSES OF HOMOPHOBIC ACTIONS AND ALMOST 90% OF LESBIANS, GAYS, BISEXUALS AND TRANS PEOPLE (LGBT) HAVE EXPERIENCED IT. IN THIS SAMPLE, THE MAIN PROBLEM OF HOMOPHOBIA IS EXPRESSED BY MOCKERIES AND INSULTS FROM PEOPLE WHO ARE NOT ACQUAINTED WITH THE VICTIMS. KEY WORDS: HOMOPHOBIA, SEXUAL ORIENTATION, GENDER IDENTITY